Impact of Intermittent Fasting on Metabolic Syndrome Reversal in Older Adults - Shakir, Adnan Saeed; Mustafa, Mehr Un Nisa; Abdul Baqi; Akhter, Aisha; Begum, Zubia; Shamraz, Hinza (Indus Journal of Bioscience Research, 2025)
Background: The reasons behind the increased prevalence of metabolic syndrome in older individuals are cumulative metabolic stress, a drop in insulin sensitivity, and inactive lifestyles. Intermittent fasting has become one of the possible non-pharmacological approaches, although the evidence was scarce in older age groups. Objective: To evaluate the impact of a structured intermittent fasting regimen on metabolic syndrome reversal and related metabolic parameters in older adults. Methodology: The prospective interventional study was planned to take place between November 2024 and May 2025 at the department of Endocrinology, Services Hospital, Lahore, Pakistan. A total of seventy two adults between the ages of 60 years and older with metabolic syndrome were enrolled. The subjects were put on a 16:8 intermittent fasting program in 12 weeks. Before and after the intervention, anthropometric measurements and glycemic parameters, lipid profile, and blood pressure were monitored. Paired statistical tests were used in comparing outcomes. Results: Intermittent fasting was associated with great weight, BMI, waist circumference, fasting glucose and HbA1c, insulin resistance, total cholesterol, LDL, triglycerides, systolic and diastolic blood pressure reductions (all p < 0.05). Twenty-five percent of the participants had full reversal of their metabolic syndrome and 58% had partial improvement. Compliance was excellent and negative events were low and mild. Conclusion: There were significant changes in metabolism observed with intermittent fasting and some degree of recovery or complete recovery of metabolic syndrome in a considerable percentage of older adults. The regimen was highly accepted and can provide an effective lifestyle intervention to reduce the metabolic risk in ageing communities.